USE OF MULTICRITERIA ANALYSIS TO MEASURE THE EFFECTIVENESS OF STRATEGIC PROCESSES IN COMPANIES OF SERVICES PUBLIC - Arboleda Zúñiga, Jairo; Arias , Laura V. (Universidad Pontificia Bolivariana, 2020)
This article focuses on the design and implementation of a methodology for evaluating the effectiveness of strategic processes in a public service company, in which operational and administrative factors are taken into account; By incorporating quantitative tools for multicriteria analysis and process analysis, an innovative quantitative model is developed with reliable results to improve the management of processes, so that the level of user satisfaction is increased, increasing the profitability of the company and adjusting processes efficiently to the requirements of the quality system in public management.